Family Functioning and Optimism as Protective Factors of Life Satisfaction Among Stroke Patients During the COVID-19 Epidemic in Shenyang, China - Song, Yuequn; Cui, Can; Jia, Yajing; Zhang, Weiyu; Meng, Lifang; Sznajder, Kristin K.; Xu, Yuanyuan; Yang, Xiaoshi (Frontiers in Public Health, 2022)
The coronavirus disease-19 (COVID-19) pandemic may result in detrimental consequences for stroke patient's wellbeing. Family functioning and optimism could help stroke patients cope with crises leading to possible improvements in life satisfaction. This study aims to explore the protective effects of family functioning and optimism on life satisfaction among stroke patients during the COVID-19 pandemic in China. This study was designed as a cross-sectional survey. A total of 207 stroke inpatients who were receiving pharmacotherapy and rehabilitation in general public hospital of Liaoning province during the COVID-19 pandemic in China were consecutive selected and interviewed by online questionnaires via the WeChat platform effectively from April 8 to 30, 2020. The scales included: Satisfaction with Life Scale (SWLS), Family Adaptation, Partnership, Growth, Affection, and Resolve (APGAR) Scale and Revised Life Orientation Test (LOT-R). Hierarchical multiple regression (HMR) analysis was conducted to test the associated factors of life satisfaction. Stroke patient's life satisfaction was at a high level (Mean = 26.46, SD = 6.23) during the pandemic. Stroke patient's residence, duration of stroke, stroke type, and community shut down measures were the strong predictors of life satisfaction. Family functioning and optimism increased life satisfaction among stroke patients. This study contributes to the research on the association between family functioning and optimism on life satisfaction among stroke patients during the COVID-19 pandemic. Interventions that improve family functioning and enhance optimism should be provided in order to elevate life satisfaction for stroke patients.